Implementación del plan de comunicaciones del proyecto "escalando la adaptación basada en ecosistemas (ABE) de montaña: construyendo evidencia, replicando éxitos e informando políticas" - Correa Tinoco, Andrea Romina (2022)
The present report describes the implementation of the communications plan of the climate change adaptation project Scaling Mountain Ecosystem-based Adaptation: Building Evidence, Replicating Successes and Informing Policy, which aimed to contribute to the consolidation of the project. It focuses on the social marketing campaigns that were implemented. The campaigns called "Campaigns for Conservation (C4C)" were carried out in the cattle ranching communities of the Nor Yauyos Cochas Landscape Reserve, located in the regions of Lima and Junín. The campaigns promoted the participation of ranchers in the selection, development, adaptation and dissemination of best practices for pasture, water and livestock management. Based on my work experience, I consider that implementing social marketing campaigns in this type of projects is necessary to generate short, medium and long term changes that contribute to cushioning the impacts of climate change.